Legal Aspects of the Policy of Decarbonisation of the Transport Sector of the Economy of EU Member States - KIRYK, Alla (University Scientific Notes, 2022)
The legal aspects of the policy of decarbonisation of the transport sector of the economy of the Member States of the European Union are examined. The main international act to combat global warming (the Paris climate agreement) is examined. The European Green Deal, introduced under the terms of the 2015 Paris Climate Agreement to limit global annual temperature rise to 1.5°C, is taken into account, which is a prerequisite for achieving climate neutrality. It is noted that the European Green Agreement aims to increase the share of multimodal transport services; production and use of alternative fuels in all modes of transport; reducing air pollution in cities caused by the transport sector. The key policies of the member states of the European Union in the field of decarbonisation of the transport sector are considered: the policy of promoting the increase of the average load of vehicles through their shared use; congestion charge policy; the policy of promoting bicycle and pedestrian zones; city-wide ban on gasoline/diesel vehicles; the policy of reducing emission norms. The Fit for 55 package is studied — a set of legislative proposals to reduce greenhouse gas emissions in the EU by at least 55 % by 2030. Ukraine’s course on decarbonisation is considered. It is determined that by signing and ratifying the Paris Agreement, Ukraine has taken a course towards decarbonisation, it is also determined that climate change issues are regulated by the Association Agreement between Ukraine and the EU. The impact of the National Transport Strategy of Ukraine for the period up to 2030 on the process of decarbonisation of the transport sector of the Ukrainian economy is analysed. Using the example of the policies of the Member States of the European Union, a number of initiatives are proposed that will enable better integration of electric transport in the future. Significantly reducing greenhouse gas emissions into the atmosphere and achieving climate neutrality are found to have long-term positive effects on human health and well-being, protection of biodiversity and natural resources.
Keywords: EU transport policy; common transport policy; decarburization; European Green Agreement